Dose‐finding designs using a novel quasi‐continuous endpoint for multiple toxicities. (21st January 2013) - Ezzalfani, Monia; Zohar, Sarah; Qin, Rui; Mandrekar, Sumithra J.; Deley, Marie‐Cécile Le
<x xml:space="preserve">Abstract</x> The aim of a phase I oncology trial is to identify a dose with an acceptable safety profile. Most phase I designs use the dose‐limiting toxicity, a binary endpoint, to assess the unacceptable level of toxicity. The dose‐limiting toxicity might be incomplete for investigating molecularly targeted therapies as much useful toxicity information is discarded. In this work, we propose a quasi‐continuous toxicity score, the total toxicity profile (TTP), to measure quantitatively and comprehensively the overall severity of multiple toxicities. We define the TTP as the Euclidean norm of the weights of toxicities experienced by a patient, where the weights reflect the relative clinical importance of each grade and toxicity type. We propose a dose‐finding design, the quasi‐likelihood continual reassessment method (CRM), incorporating the TTP score into the CRM, with a logistic model for the dose–toxicity relationship in a frequentist framework. Using simulations, we compared our design with three existing designs for quasi‐continuous toxicity score (the Bayesian quasi‐CRM with an empiric model and two nonparametric designs), all using the TTP score, under eight different scenarios. All designs using the TTP score to identify the recommended dose had good performance characteristics for most scenarios, with good overdosing control. For a sample size of 36, the percentage of correct selection for the quasi‐likelihood CRM ranged from 80% to 90%, with similar results for the quasi‐CRM design. These designs with TTP score present an appealing alternative to the conventional dose‐finding designs, especially in the context of molecularly targeted agents. Copyright © 2013 John Wiley & Sons, Ltd.